Impacts of the global financial and economic crisis on the agro-food industry and rural livelihoods in Serbia - Hamid El Bilali; Biljana Panin; Sinisa Berjan; Noureddin Driouech; Aleksandra Despotovic; Nicola M. Zucaro (Apstract: Applied Studies in Agribusiness and Commerce, 2012)
Sixty-five per cent of the Serbian land area is agricultural and 55% of the population is rural.Agriculture share of GDP is more than 10% and about 47% of the rural labour force deals with agriculture. The aim of this work is to analyse the impacts of the global financial and economic crisis on the Serbian agro-food sector and rural communities. Measures introduced, mainly by public institutions, for relieving the consequences of the crisis are presented and discussed. Easily accessible yet high quality data from the central Office of Statistics in Serbia and specialized literature have been used. Impacts have been assessed by analyzing and discussing the trends of many socio-economic indicators. The crisis has had general impacts on the Serbian economy (low GDP growth, unemployment increase, price volatility, purchasing power decrease, etc.). Due to the crisis growth in agricultural production has been very low (0.1% in 2009). Agro-food exports decreased dramatically in 2008. About 9000 agricultural jobs were lost in 2008 and 2009. Reduced exports and lower domestic demand impacted negatively on agricultural commodity prices and agricultural household incomes.Access to credit became more difficult especially for small producers. However, agriculture is still a very important safety net. Agricultural employment share has increased both for men and women. The importance of agriculture is even higher if we consider the “grey agricultural economy”. To mitigate the crisis effects, the Government provided subsidies to rural people and will adopt the National Strategic Plan and Programme for Rural Development. Nevertheless, public institutions - in partnership with private, civil society and international organisations - should improve rural producers’ access to market information and credits and foster investments in rural areas including non-agricultural ones and those aiming at improving physical capital.